2017
DOI: 10.1017/s0031182017000622
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of disease susceptibility and innate immune response between diploid and triploid Atlantic salmon (Salmo salar) siblings following experimental infection with Neoparamoeba perurans, causative agent of amoebic gill disease

Abstract: SUMMARYFew studies have focussed on the health and immunity of triploid Atlantic salmon and therefore much is still unknown about their response to commercially significant pathogens. This is important if triploid stocks are to be considered for full-scale commercial production. This study aimed to investigate and compare the response of triploid and diploid Atlantic salmon to an experimental challenge with Neoparamoeba perurans, causative agent of amoebic gill disease (AGD). This disease is economically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…As the level of basal epithelial hyperplasia increased at the centre of the lesions, hydropic degeneration of the CCs was observed, which ultimately led to formation of regional oedema and sloughing of degenerated CCs on the surface of the lesions. The subsequent presence of CCs towards the distal end of the lamellae was in accordance with previous reports in Atlantic salmon (Chalmers et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As the level of basal epithelial hyperplasia increased at the centre of the lesions, hydropic degeneration of the CCs was observed, which ultimately led to formation of regional oedema and sloughing of degenerated CCs on the surface of the lesions. The subsequent presence of CCs towards the distal end of the lamellae was in accordance with previous reports in Atlantic salmon (Chalmers et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, wax‐embedded gill tissues, obtained from a previous 4‐week AGD cohabitation challenge conducted in April 2014 at the same research facility, were used (Chalmers et al, ). Fish had been sampled at week 4 post‐challenge when fish were displaying gross gill scores of 3.5–4.5 and were grouped within the infection‐level category, Heavy (E) (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Chalmers et al [89] suggested that ploidy does not affect the manifestation or severity of AGD pathology or the serum innate immune response. Additionally, the serum immune response of diploid and triploid Atlantic salmon may not be significantly affected by AGD.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Whilst the type and physical structure of swab fibres are important, the method and area of swabbing are also relevant for successful diagnosis of AGD. Although the universal swabbing method is based on sampling of the second gill arch within research (Adams & Nowak, 2003, 2004a; Chalmers et al., 2017; Munday et al., 2001; Taylor et al., 2009; Wynne, Cook, Nowak, & Elliott, 2007; Young, Dyková, Nowak, & Morrison, 2008), worldwide aquaculture industry performs swabbing of all four gill arches. Although the swabbing of all gill arches increases the swabbing area and therefore detection of N. perurans is more likely to be successful, irritation of the gills could be greater.…”
Section: Introductionmentioning
confidence: 99%